(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2025)
We have each been inspired by the Conference title to take different ways into the topic, but the theme which unites our presentations is a focus on what we as existential practitioners can bring to an understanding of our relationship with whatever we mean when we use the term ‘wildness’. I have taken the Conference title quite literally as an invitation to reflect on how we can go into ‘the Wild Woods’, and the therapeutic value of doing so. And bearing in mind this is the ‘Existential Movement’ conference, I will begin by focusing on what some of the existential founding philosophers have written about the importance of movement, and specifically physical exercise such as walking, and then I will go on to consider how this can impact on our relationship to our meaning world. In the course of this I will draw on the Four Worlds model, initially with regard to our relationship with the Umwelt, or physical dimension, but I will also briefly consider how a change in one dimension has more far-reaching implications for our relationship with all four dimensions of human living.